2019
DOI: 10.3389/fonc.2019.00355
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal and Cutaneous Human Papillomavirus Infections and Cancer Biology

Abstract: Papillomaviridae is a family of small non-enveloped icosahedral viruses with double-stranded circular DNA. More than 200 different human papillomaviruses (HPVs) have been listed so far. Based on epidemiological data, a subgroup of alphapapillomaviruses (alpha HPVs) was referred to as high-risk (HR) HPV types. HR HPVs are the etiological agents of anogenital cancer and a subset of head and neck cancers. The cutaneous HPV types, mainly from beta and gamma genera, are widely present on the surface of the skin in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
212
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(218 citation statements)
references
References 304 publications
(321 reference statements)
2
212
0
4
Order By: Relevance
“…The CDKN1A gene, which encodes for the cyclin-dependent kinase inhibitor p21, is a transcriptional target of the tumor suppressor protein p53 and functions to induce cell cycle arrest in the event of DNA damage [35,36]. In the context of HPV type, it appears to be that the alphapapillomaviruses, including the low-risk HPV2 and HPV57 and the high-risk HPV15 and HPV18, target the p53-p21 pathway regardless of oncogenic potential [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The CDKN1A gene, which encodes for the cyclin-dependent kinase inhibitor p21, is a transcriptional target of the tumor suppressor protein p53 and functions to induce cell cycle arrest in the event of DNA damage [35,36]. In the context of HPV type, it appears to be that the alphapapillomaviruses, including the low-risk HPV2 and HPV57 and the high-risk HPV15 and HPV18, target the p53-p21 pathway regardless of oncogenic potential [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, most of the oncogenic viruses possess the capability to inhibit autophagy mainly promoting viral replication and cellular maintenance, though this favors cancer onset. epithelial cancers (Gheit, 2019). Similar to HBV and MCPyV, HPV is involved in carcinogenesis in a state called "pseudolatency, " where the viral genome is integrated in the host cells, produces oncoviral proteins, and drives mutagenesis, although unable to replicate (Chang et al, 2017).…”
Section: Cutaneous and Mucosal Oncogenic Viruses Human Papilloma Virumentioning
confidence: 99%
“…It was revealed that chronic exposure to ultraviolet radiation (UVR) accelerates skin aging and even may lead to the development of melanoma and nonmelanoma skin cancers (Reich & Mędrek, 2013). There is growing evidence of an etiological role of betapapillomaviruses (β HPVs) in non-melanoma skin cancer (NMSC), together with UVR (Gheit, 2019;Hasche, Stephan, Braspenning-Wesch, et al, 2017). But NBUVB is an exception.…”
Section: Case Reportmentioning
confidence: 99%